One of the northernmost records of Eleocharis mamillata subsp. mamillata (Cyperaceae) in Europe, and the first discovery in Murmansk Region (Russia) - Blinova, Ilona V.; Gregor, Thomas (Memoranda Societatis pro Fauna et Flora Fennica, 2016)
We report the first locality (67°55’13” N, 33°39’73” E) in Murmansk Region of Eleocharis mamillata H. Lindb. f. subsp. mamillata. The species distribution range in Europe extends to nearly 68° N attested by one older (1924) record in Finland and two recent ones (2008–2009) in Norway. The new site at a similar latitude in Lapponia Imandrae in Russia is briefly described. It is proposed to include this species in the next regional Red Data Book in the group ”In need of monitoring”.